Parallel implementation of a randomized regularized Kaczmarz’s algorithm - Zhdanov, A.; Sidorov, Y. (Kompʹûternaâ optika, 2015)
The article describes the parallel implementation of a randomized regularized Kaczmarz's algorithm. By way of illustration, the randomized parallel version of the algorithm is used for solving the Fredholm integral equation of the first kind with a perturbed right-hand side, showing that in this way the computation speed can be increased up to 4 times as compared to the sequential randomized version.